2014
DOI: 10.1186/s13049-014-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel algorithm for primary mass casualty triage by paramedics in a physician manned EMS system: a dummy based trial

Abstract: BackgroundThe Amberg-Schwandorf Algorithm for Primary Triage (ASAV) is a novel primary triage concept specifically for physician manned emergency medical services (EMS) systems. In this study, we determined the diagnostic reliability and the time requirements of ASAV triage.MethodsSeven hundred eighty triage runs performed by 76 trained EMS providers of varying professional qualification were included into the study. Patients were simulated using human dummies with written vital signs sheets. Triage results we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
1
21
0
3
Order By: Relevance
“…Distributive justice refers to fairness in the distribution of limited resources and benefits. Although triage tools may support A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 14 and improve the quality of critical care admission decisions, they probably cannot and should not supplant intensivists' experience and clinical judgment in decision making.…”
Section: What Other Factors Should Influence the Decision To Admit Amentioning
confidence: 99%
“…Distributive justice refers to fairness in the distribution of limited resources and benefits. Although triage tools may support A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 14 and improve the quality of critical care admission decisions, they probably cannot and should not supplant intensivists' experience and clinical judgment in decision making.…”
Section: What Other Factors Should Influence the Decision To Admit Amentioning
confidence: 99%
“…Most reports investigating the effectiveness of education concerning mass casualty incidents have conducted pre-and post-test evaluations, just after the course ended. [5][6][7][8] This study was not a pre-and post-test study but a comparative study of observations from independent groups. However, in the present study, we found that education concerning mass casualty incidents was effective in improving performance even though the evaluation was not performed immediately after the education.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from all study participants. Triage training and data acquisition was performed as reported previously in detail [ 3 , 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Amberg-Schwandorf Algorithm for Primary Triage (ASAV, Amberg-Schwandorf-Algorithmus für die Vorsichtung ) (Fig. 1 ) served as triage algorithm for this purpose [ 3 , 4 , 6 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation